ANALISIS PEMASARAN KETERHUBUNGAN TERHADAP LOYALITAS PELANGGAN (Studi Pada Mobil Toyota Avanza di Nasmoco Siliwangi) - Sri Wibowo, 13.05.51.0042; Marlien, Marlien (Students Journal of Economic and Management, 2018)
The purpose of this study to determine the influence of trust, commitment and communication to customer loyalty at PT. Nasmoco Siliwangi Semarang. The population is a number of individuals who have the same nature or interests. In this study the population is consumers who buy Toyota Avanza car products at PT. Nasmoco Siliwangi Semarang in 2016 as many as 974. The sample in this study as many as 91 consumers who buy the Toyota Avanza products at PT. Nasmoco Siliwangi and have been using Toyota Avanza minimal 2 years, where in this research sampling method that is purposive sampling that is sampling based on criteria specified that consumers who buy Toyota Avanza car products at PT. Nasmoco Siliwangi, and owns a Toyota Avanza car at PT. Nasmoco Siliwangi. Methods of data analysis using multiple regression. The results showed that there is a positive and significant influence between the Trust on Customer Loyalty, there is a positive and significant influence between Commitment to Customer Loyalty and there is a positive and significant influence between the Communication on Customer Loyalty...Keywords: Trust, commitment, communication and customer loyalty